A study of XML in the Library Science Curriculum in Taiwan and South East Asia / Naicheng Chang, Yuhui Huang and Alan Hopkinson - Chang, Naicheng; Huang, Yuhui; Hopkinson, Alan (2011)
This paper aims to investigate the current XML-related courses available in 96 LIS schools in South East Asia and Taiwan's 9 LIS schools. Also, this study investigates the linkage of library school graduates in Taiwan who took different levels of XML-related education (that is XML arranged as an individual course or XML arranged as a section unit in courses) and their professional qualification. Research questions include what is the availability of XML-related courses in countries in Taiwan and South East Asia? What are Taiwan LIS graduates' views on degree of XML-related courses satisfaction, cognition of learning XML technology, and views of XML-related courses? What is the linkage of Taiwan LIS graduates who studied different levels of XML-related education and their professional qualifications? This study applies 3 research methodologies: information gathering from the internet; questionnaire surveys; in-depth interviews. Results of the analysis show that LIS schools should provide optional XML-related courses with practical sessions, and library associations should provide regular XML-related continuing education to enhance LIS students' professional qualifications.